2019
DOI: 10.1371/journal.pone.0214728
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum 25-hydroxyvitamin D and diabetic kidney disease in Chinese patients with type 2 diabetes

Abstract: Objective The objective was to assess the association between 25-hydroxyvitamin D (25OHD) level and diabetic kidney disease (DKD) in Chinese patients with type 2 diabetes. Methods Data pertaining to 351 in-patients with type 2 diabetes were collected. Subjects were classified into three groups based on the level of urinary albumin-to-creatinine ratio (UACR). UACR < 30 mg/g was defined as normoalbuminuria, while UACR levels of 30–300 mg/g and ≥ 300 mg/g were defined as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 42 publications
4
39
0
Order By: Relevance
“…However, clinical studies pertaining to the association between vitamin D status and DKD have reported inconsistent results. A recent cross-sectional study of 351 Chinese inpatients with T2DM demonstrated that VDD was independently associated with DKD [21]. This was consistent with many previous studies which had linked albuminuria to low vitamin D levels [58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, clinical studies pertaining to the association between vitamin D status and DKD have reported inconsistent results. A recent cross-sectional study of 351 Chinese inpatients with T2DM demonstrated that VDD was independently associated with DKD [21]. This was consistent with many previous studies which had linked albuminuria to low vitamin D levels [58][59][60][61][62].…”
Section: Discussionsupporting
confidence: 86%
“…A Chinese cross-sectional survey among diabetic inpatients reported that the proportions of persons with VDD were 83.5%, the recruitment center of which was located in north China (latitude 34°-37° N) [33]. Besides, approximately 62.7% of T2DM subjects were affected in two epidemiological studies conducted in Nanjing, which is located in eastern coastal China (latitude 31°-33° N) [21]. In present study, we found that the prevalence of VDD was about 71.7% among this study population with T2DM, who were recruited in Changsha, a city located in central China (latitude 27°-29° N).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Chinese cross-sectional survey among diabetic inpatients reported that the proportions of persons with VDD were 83.5%, the recruitment center of which was located in north China (latitude 34 • -37 • N) (36). Besides, ∼62.7% of T2DM subjects were affected in two epidemiological studies conducted in Nanjing, which is located in eastern coastal China (latitude 31 • -33 • N) (19). In present study, we found that the prevalence of VDD was about 71.7% among this study population with T2DM, who were recruited in Changsha, a city located in central China (latitude 27 • -29 • N).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, the association between vitamin D deficiency (VDD) and other nonclassical outcomes besides skeletal disorders has drawn increasing attention, especially diabetes and diabetes-related complications (14)(15)(16)(17). The inverse association between vitamin D levels and risk of DR (18), DKD (19), or DFU (20) among diverse populations has been demonstrated, whereas other studies reported discordant results regarding the correlations between vitamin D status and these three complications of diabetes (21)(22)(23). More importantly, large-scale epidemiological studies on the association of VDD and diabetes-related complications among the Chinese population are scarce (24,25), which have revealed that lower vitamin D level was associated with increased albuminuria/creatine ratio and higher risk of DR. And no study has evaluated the relationship between VDD and DFU in Chinese diabetic population.…”
Section: Introductionmentioning
confidence: 99%